Manuela Sáenz: da história às ressignificações ficcionais – um percurso da colonialidade à descolonização e à decolonialidade - Rohde, Marina Luísa (2022)
Based on the studies of hybrid narratives of history and fiction inserted in the context of the Research Group “Reframing of the past in America: processes of reading, writing and translation of hybrid genres of history and fiction – ways to decolonization”, we analyze the reinterpretations of the empirical figure of Manuela Sáenz (1795 – 1856) from socio-historical and literary paths by means of a bibliographical and documentary research, with a comparative and qualitative nature. In this way, we seek to show that literary art is the space in which, potentially, the characters minimized by the positivist historical discourse are re-signified. In this process, we established, in addition to comparing three biographies, a synchronic trajectory of novels written in America that portray Manuela Sáenz as the protagonist, as well as the analysis of two historical novels. The corpus that underlies our study is inserted in an inter-American context, more precisely in the United States, Ecuador and Argentina. Thus, the chosen biographical productions are Manuela Sáenz La Libertadora del Libertador ([1944] 1978), by Alfonso Rumazo González; The Four Seasons of Manuela: The Love Story of Manuela Sáenz and Simón Bolívar ([1952] 1966), by Victor Wolfang Von Hagen and For Glory and Bolívar: the remarkable life of Manuela Sáenz (2008), by Pamela S. Murray. Regarding the hybrid narratives of history and fiction, the selected novels are Manuela (1991 [2000]), by Luís Zúñiga and La Gloria eres tú ([2004] 2019), by Silvia Miguens. The selection of this corpus considered criteria such as the presence or absence of the critical and questioning element of the official records through narratives that expose credible points of view, capable of reframing or corroborating Eurocentric models of apprehension of the past. We also associate the concepts of coloniality, decolonization and decoloniality with the ideologies present in the different modalities of historical novels based on the theoretical assumptions of Mignolo (2012, 2016, 2017). In addition, we point out the interest in Manuela Sáenz's protagonism and the insertion of these narratives in the Ecuadorian and Argentine space. The theoretical support of this approach, both to the historical personality and to the different modalities of the historical novel, finds support in the studies of Aínsa (1991), Menton (1993), Márquez Rodríguez (1996), Chambers (2001), Fernández Prieto (2003), Hennes (2005), Murray (2006; 2008) Fleck (2011; 2017), among others. Our research shows that Sáenz's representation to America comprises a tangle of discourses that are at odds with each other, giving her figurations between lover and crazy or political and diplomatic. Therefore, Manuela Sáenz's scriptural figurations, whether in biographies or novels, reveal a journey between coloniality and decolonization with paths that glimpse decoloniality.